2018
DOI: 10.1155/2018/8206381
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management Associated with Posttraumatic Unilateral Temporomandibular Joint Anterior Disc Displacement: A Case Report and Literature Review

Abstract: The aim of the present article is to review the etiological risk factors and the general and oral management of anterior disc displacement with reduction caused by a chin trauma, and to describe the diagnostic process and the treatment provided to an affected 7-year-old girl. The patient also experienced frequent and severe cephaleas, which may be related to cervical vertebrae deviation. The patient was successfully treated with an intraoral occlusal splint and analgesics. Pediatric dentists must always be awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…5 On the other hand, there is controversy regarding the definite evidence and the necessity of management of traumatic TMJ conditions because the complications of trauma to the TMJ are not always apparent immediately after the injury. 1,3,4,[6][7][8][9][10] Magnetic resonance imaging (MRI) can evaluate the characteristics of the condylar structure and soft tissue components of the TMJ accurately, such as hemarthrosis, effusion, capsular tear, and edema of the retrodiscal tissue. 11,12 Westesson and Brooks reported that 7% of 261 symptomatic TMJ patients without disc derangement showed the high signal intensity in the TMJ but the high signals were not shown in 11 asymptomatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…5 On the other hand, there is controversy regarding the definite evidence and the necessity of management of traumatic TMJ conditions because the complications of trauma to the TMJ are not always apparent immediately after the injury. 1,3,4,[6][7][8][9][10] Magnetic resonance imaging (MRI) can evaluate the characteristics of the condylar structure and soft tissue components of the TMJ accurately, such as hemarthrosis, effusion, capsular tear, and edema of the retrodiscal tissue. 11,12 Westesson and Brooks reported that 7% of 261 symptomatic TMJ patients without disc derangement showed the high signal intensity in the TMJ but the high signals were not shown in 11 asymptomatic patients.…”
Section: Introductionmentioning
confidence: 99%